General anesthesia and neurotoxicity on the developing brain - Gabriele Finco; Paolo Mura; Andrea Corona; Maurizio Evangelista; Salvatore Sardo (Hygeia Press di Corridori Marinella, 2018)
With the evolution of surgical techniques and technology an increasing number of infants, neonates, and fetuses are exposed to general anesthesia. Despite the acknowledged safety of general anesthesia, a considerable amount of preclinical evidence shows that the developing brain is highly vulnerable to anesthetic drugs. Early-age anesthesia may impair the fine tuning of neurotransmitters and growth factors that orchestrate the replication, differentiation and organization of neural cells into functional networks. In order to translate these insights from animal models to human patients, large trials and observational studies have been published or are currently ongoing. The aim of this narrative review is to provide an update on the pathophysiologic mechanisms and published evidence of anesthesia-related neurotoxicity in pediatric patients.